Another new Cyrtodactylus (Squamata: Gekkonidae) from Guwahati, Assam, India - Purkayastha, Jayaditya; Das, Madhurima; Bohra, Sanath Chandra; Bauer, Aaron M.; Agarwal, Ishan (Zootaxa, 2020)
We describe a new species of Cyrtodactylus from Guwahati city in the state of Assam, India and provide additional data on the recently described Cyrtodactylus guwahatiensis. Cyrtodactylus urbanus sp. nov. falls in the newly defined khasiensis group within the Indo-Burma clade of Cyrtodactylus and is the poorly supported sister taxon to Cyrtodactylus khasiensis. The new species differs from other members of the khasiensis group in mitochondrial sequence data (12.5–17.1 % uncorrected pairwise ND2 sequence divergence) as well as aspects of morphology including the number and arrangement of precloacal pores in males, the number of mid-ventral scales and paravertebral tubercles, and colour pattern. This is the second Cyrtodactylus endemic to the Guwahati region, the fourth from Assam and the twelfth from Northeast India.